Perioperative and Pathological Outcome of Nerve-Sparing Radical Cystectomy With Ileal Neobladder - Vogt, Katharina; Netsch, Christopher; Becker, Benedikt; Oye, Sebastian; Gross, Andreas J.; Rosenbaum, Clemens M. (Frontiers in Surgery, 2021)
Purpose: So far, it is not described whether the perioperative course and the pathologic outcome of patients who undergo radical cystectomy (RC) with orthotopic bladder substitution (OBS) differs if nerve sparring (NS) is performed or not. Material and methods: In all, 472 patient who underwent RC between 2012 and 2019 at our department. We performed a retrospective analysis of 116 patients who underwent RC with ileal neobladder. We analysed perioperative complications according to the Clavien-Dindo classification system as well as the pathological outcome. Results: Of 116 patients, 68 (58.6%) underwent RC and 48 (41.4%) underwent NS-RC. Clavien-Dindo complications ≥3b occurred in 15 (12.9%) of all patients. Only infectious complications differed among the groups (NS-RC: 25 pts (52.1%) vs RC: 20 pts (29.4%); p=0.02). There was no significant difference concerning tumor stage. Concomitant Cis was present in 24 patients (35.3%) of the RC and in 27 patients (56.3%) of the NS-RC group (p=0.036). Nodal status and positive surgical margin status of the bladder tumor did not differ among groups. In all, 42 of all male patients (45.7%) had an incidental prostatic carcinoma. Positive surgical margins concerning the prostate carcinoma occurred in 6 patients, with all cases in the RC group (p=0.029). Conclusions: Our data suggest that performing NS during RC in carefully selected patients is a safe procedure and does not impair perioperative outcome. Pathological outcome of NS-RC is comparable as well.